Literary monographs. - University of Wisconsin. Department of English; University of Wisconsin--Madison. Department of English ([Madison] University of Wisconsin Press, 1967)
Irregular
Published for the Dept. of English, University of Wisconsin--Madison (1967- under the earlier name: Dept. of English, University of Wisconsin).
Keywords: English literature; American literature